2018
DOI: 10.1007/s00404-018-4896-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a quantitative system for real-time measurement of postpartum blood loss

Abstract: The technique of real-time measurement of postpartum blood loss after vaginal delivery as presented in this study is practicable, reliable and strongly correlated with the actual blood loss and, therefore, poses an actual improvement in the management of PPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 19 publications
3
33
0
1
Order By: Relevance
“…Our institution uses a proprietary, validated quantitative system to measure vaginal delivery blood loss 21,22 . Immediately after clamping the cord, the midwife places a fresh drape under the woman's pelvis to collect blood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our institution uses a proprietary, validated quantitative system to measure vaginal delivery blood loss 21,22 . Immediately after clamping the cord, the midwife places a fresh drape under the woman's pelvis to collect blood.…”
Section: Methodsmentioning
confidence: 99%
“…The drape is regularly checked and if continued bleeding is observed, the drape is weighed on a neonatal balance installed in every suite. If the overall weight (ie, fluid minus drape) exceeds 300 g, a plastic bag with a quantitative scale is placed under the pelvis for blood collection and exact measurement 21,22 . Cesarean blood loss is estimated by the obstetrician; all fluid between hysterotomy and clamping the cord is collected in a pouch and presumed to be mostly amniotic in origin.…”
Section: Methodsmentioning
confidence: 99%
“…QBL measurement was defined as the combined blood loss from all gravimetric and volumetric sources and was continued until the treating clinicians were confident that abnormal bleeding had stopped. The gravimetric technique included weighing all blood soaked swabs and under-buttocks incontinence bed pads and subtracting their known dry weight and has been previously described [8,15,20]. At unassisted vaginal delivery, underbuttocks incontinence pads were changed immediately after delivery to discard amniotic fluid, and subsequent fluid on new pads was assumed to be blood and therefore measured.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative blood loss (QBL) measurement, using gravimetric and volumetric techniques, is more accurate than visual estimation, both in simulations and clinical practice [10,13,15,19,20] and so gives a more representative and reproducible measure of the incidence and severity of PPH, although all methods have shortcomings. It remains unclear, however, whether quantitative measurement is feasible in all clinical settings, after all types of deliveries and outside of routine hours.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported overestimations of blood loss at low volumes and underestimations at high volumes after vaginal delivery using visual estimation methods [13]. Currently, there are no reliable tools to measure the amount of postpartum blood loss [10,14,15]. Tourne et al used a plastic bag to collect and measure the volume of blood loss after delivery and investigated the correlation between the bag's volume and hemoglobin and hematocrit levels.…”
Section: Discussionmentioning
confidence: 99%